Meta‐modeling soil organic carbon sequestration potential and its application at regional scale. Issue 2 (1st March 2013) - Luo, Zhongkui; Wang, Enli; Bryan, Brett A.; King, Darran; Zhao, Gang; Pan, Xubin; Bende-Michl, Ulrike
Abstract : Upscaling the results from process‐based soil–plant models to assess regional soil organic carbon (SOC) change and sequestration potential is a great challenge due to the lack of detailed spatial information, particularly soil properties. Meta‐modeling can be used to simplify and summarize process‐based models and significantly reduce the demand for input data and thus could be easily applied on regional scales. We used the pre‐validated Agricultural Production Systems sIMulator (APSIM) to simulate the impact of climate, soil, and management on SOC at 613 reference sites across Australia's cereal‐growing regions under a continuous wheat system. We then developed a simple meta‐model to link the APSIM‐modeled SOC change to primary drivers, i.e., the amount of recalcitrant SOC, plant available water capacity of soil, soil pH, and solar radiation, temperature, and rainfall in the growing season. Based on high‐resolution soil texture data and 8165 climate data points across the study area, we used the meta‐model to assess SOC sequestration potential and the uncertainty associated with the variability of soil characteristics. The meta‐model explained 74% of the variation of final SOC content as simulated by APSIM. Applying the meta‐model to Australia's cereal‐growing regions reveals regional patterns in SOC, with higher SOC stock in cool, wet regions. Overall, the potential SOC stock ranged from 21.14 to 152.71 Mg/ha with a mean of 52.18 Mg/ha. Variation of soil properties induced uncertainty ranging from 12% to 117% with higher uncertainty in warm, wet regions. In general, soils in Australia's cereal‐growing regions under continuous wheat production were simulated as a sink of atmospheric carbon dioxide with a mean sequestration potential of 8.17 Mg/ha.